2021
DOI: 10.1039/d1sc02161c
|View full text |Cite
|
Sign up to set email alerts
|

Direct decarboxylation of ten-eleven translocation-produced 5-carboxylcytosine in mammalian genomes forms a new mechanism for active DNA demethylation

Abstract: DNA cytosine methylation (5-methylcytosine, 5mC) is the most important epigenetic mark in higher eukaryotes. 5mC in genomes is dynamically controlled by the writers and erasers. DNA (cytosine-5)-methyltransferases (DNMTs) are responsible...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
0
27
0
1
Order By: Relevance
“…5 The resulting 5fC and 5caC undergo base excision repair or direct deformylation or decarboxylation to restore unmodied cytosines. [5][6][7][8][9] The discovery of 5hmC in mammalian genomes is a landmark in epigenomics study. 10 Similar to 5mC in DNA, 5hmC is also viewed as a vital epigenetic marker that could modulate gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…5 The resulting 5fC and 5caC undergo base excision repair or direct deformylation or decarboxylation to restore unmodied cytosines. [5][6][7][8][9] The discovery of 5hmC in mammalian genomes is a landmark in epigenomics study. 10 Similar to 5mC in DNA, 5hmC is also viewed as a vital epigenetic marker that could modulate gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…0.0004%) are low, they fall within a similar range to those determined in different mammalian tissues (0.00004–0.0005%; [ 6 ]) ( figure 1 d ). The relatively weak TET activity towards 5caC generation, as reported by in vitro analysis of C. cinerea TET proteins on DNA [ 71 ], might be responsible for the lowest amounts of 5carC among all oxi-mCs, or 5caC might be actively removed from DNA and RNA by excision mechanisms, such as thymine DNA glycosylases or direct decarboxylation to cytosine [ 72 ]. However, to date, the activity of thymine DNA glycosylases (a potential gene was predicted in C. cinerea ; [ 29 ]) or other excision mechanisms have not yet been discovered in fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Without clear identification of the biological entity responsible for the process, we cannot completely rule out that unknown processes other than intragenomic decarboxylation are responsible for the measured data. During the review process of this manuscript Feng and co‐workers showed an incorporation of the F‐carboxycytosine as a nucleoside and interestingly managed to detect the decarboxylation of cadC to dC much earlier on [29] …”
Section: Figurementioning
confidence: 99%
“…During the review process of this manuscript Feng and co‐workers showed an incorporation of the F‐carboxycytosine as a nucleoside and interestingly managed to detect the decarboxylation of cadC to dC much earlier on. [29] …”
mentioning
confidence: 99%